Microperforated Acoustic Metasurfaces for Low-Frequency Broadband Noise Reduction - Wang, Jiayu (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2025)
This thesis focuses on the development of microperforated acoustic metasurfaces to address the challenges of achieving low-frequency, broadband noise reduction in compact configurations, with specific applications in aeroengine noise control. The work is motivated by the stringent space and weight constraints in aeroengine and duct systems, where efficient sound absorption is crucial. A multi-chamber microperforated panel absorber (MC-MPPA) was proposed to enable multiple acoustic resonances within a limited volume, thereby broadening the absorption bandwidth. A two-point impedance method (TpIM), grounded in acoustic network theory, was developed to model and optimise the absorber's impedance characteristics. Experimental validation showed that MC-MPPA samples achieve absorption coefficients exceeding 0.8 across two distinct frequency bands: 397-1000 Hz and 698-1895 Hz, corresponding to subwavelength ratios of 1/18.2 and 1/10.5, respectively. To further enhance low-frequency absorption, particularly below 500 Hz, a new class of microperforated acoustic metasurfaces incorporating extended-neck Helmholtz resonators was introduced. Three configurations were designed and 3D-printed, exhibiting remarkable subwavelength performance. For instance, a deep subwavelength configuration achieved over 97% absorption at 150 Hz, corresponding to a subwavelength ratio of 1/48. A broadband-optimised configuration demonstrated an average absorption coefficient exceeding 0.74 in the 300-500 Hz range with a thickness of only 27.5 mm, and over 0.88 in the 543-945 Hz range with a thickness of just 26.2 mm. In addition, internal perforated partitions enhance the acoustic performance of the optimised MC-MPPA at higher frequencies and lower porosities (e.g., 0.5%-1.0% within 20-3000 Hz), enabling superior absorption with fewer surface perforations. This effectively reduces aerodynamic drag under grazing flow, making the design well-suited for aero-engine liners. To further address the practical requirements of aeroengine liner applications, the acoustic performance of the proposed designs was extended to grazing flow conditions through an impedance-based optimisation framework. A Mach-number-dependent impedance model was incorporated into the TpIM, enabling accurate prediction of impedance under flow. A Cremer-impedance-inspired cost function was employed to guide the optimisation, resulting in high-performance liners that were tested at Mach numbers up to 0.25 and sound pressure levels (SPLs) up to 140 dB. The 32 mm-thick MC-MPPA liner achieved up to 25 dB of transmission loss in the 600-2000 Hz range at an incident SPL of 140 dB and a grazing flow Mach number of 0.25. Under the same conditions, the 32 mm-thick CMHA liner achieved up to 15 dB of transmission loss below 1000 Hz. Additionally, in the absence of flow, the CMHA liner exhibited broadband transmission loss of 10-23 dB below 1000 Hz. All proposed designs and theoretical modeling methods were experimentally validated using impedance tubes and grazing flow test rigs. The strong agreement between predictions and measurements confirms the reliability of the theoretical frameworks and demonstrates the practical feasibility of 3D-printed acoustic metamaterials for real-world noise control applications. Overall, this thesis advances the state of the art in low-frequency broadband microperforated acoustic metasurfaces, supported by rigorous theoretical modeling and experimental validation. The developed solutions are compact, lightweight, and tunable, and are well suited for noise control in aeroengines and duct systems.
APPROVED
Keywords: Acoustic; Acoustic Metasurfaces; Micro-Perforated Panel Absorber; Helmholtz Resonator; Multi-Degree-of-Freedom Absorber; Acoustic Liner; Aeroengine Noise; Fan Noise Reduction; Low-Frequency Broadband Sound Reduction; Additive Manufacturing Techniques; 3D Printing Technology; Two-Point Impedance Method; Optimisation